Well London: Results of a Community Engagement Approach to Improving Health Among Adolescents from Areas of Deprivation in London. Issue 2 (3rd April 2017) - Frostick, Caroline; Watts, Paul; Netuveli, Gopalakrishnan; Renton, Adrian; Moore, Derek
ABSTRACT: This article reports findings among adolescents of the impact of Well London, a program of wellbeing interventions delivered across 20 deprived neighbourhoods of London using a community engagement model. Twelve hundred and fifty-four adolescents were surveyed from matched intervention and control areas. There was no significant intervention effect on the main outcome measures: unhealthy eating, physical activity, and mental health. Factors influencing the results may include the possibility that the communities defined by the cluster randomized controlled trial (CRCT) were not an accurate reflection of the adolescent's natural community, and interactions within the school environment in particular could have led to a dilution of effect.